Environmental concern on Geneticaly Modified Organism (GMO): a review / Mohd Faiz Aidil Khairuddin and Hamizah Othman - Khairuddin, Mohd Faiz Aidil; Othman, Hamizah (Faculty of Plantation and Agrotechnology, 2018)
Environmental concern on Genetically Modified Organism (GMO ) has become one the major issue in Europe and Asia country when the argument started argue and feared the reliability-' and potentially effect the GMO crop will harm fill to environmental .Many of the research claimed that the GM food are unnatural and give negative impacts to environmental in long term period. However, without the doubt, GMO are successfully method to support people overcome the starvation and allow plant breeders quickly to produce food depend on increasing consumer demands. This paper aimed to review on the issue regarding potential disadvantage of GMO product to environmental and to extend the concern of consumer who are worried about the impacts that GMO may have on their environmental for better precaution to the future. The introduction of GM crops around the world causes the existence of possibly adverse impacts of GMO on the environment disturbance of ecosystem and threat for biodiversity. The environmental risk assessment is necessary for every GM crops to ensure the crops developed by using modem biotechnology are protect the environment from the risk before the impact would be difficult or impossible to control.